Protein-Based Delivery Systems for Anticancer Metallodrugs: Structure and Biological Activity of the Oxaliplatin/β-Lactoglobulin Adduct - Daria Maria Monti; Domenico Loreto; Ilaria Iacobucci; Giarita Ferraro; Alessandro Pratesi; Luigi D'Elia; Maria Monti; Antonello Merlino (MDPI AG, 2022)
β-lactoglobulin is the major component of whey. Here, the adduct formed upon the reaction of the protein with oxaliplatin (OXA) has been prepared, structurally characterized by X-ray crystallography and electrospray ionization-mass spectrometry, and evaluated as a cytotoxic agent. The data demonstrate that OXA rapidly binds β-lactoglobulin via coordination with a Met7 side chain upon release of the oxalate ligand. The adduct is significantly more cytotoxic than the free drug and induces apoptosis in cancer cells. Overall, our results suggest that metallodrug/β-lactoglobulin adducts can be used as anticancer agents and that the protein can be used as a metallodrug delivery system.